The Effect of Rock Phosphate on Soil Nutrient Dynamics, Growth, Development and Yield of Oil Palm in The Semi-Deciduous Forest Zone of Ghana (Journal of Science and Technology, 2016)
Field experiment was conducted at Oil Palm Research Institute, Kusi from 2002 to 2007 to as-sess the effect of Phosphate Rock (PR) on soil nutrient dynamics, growth, development and yield of oil palm. The study was carried out on the soils of Nzema series classified as Ferric Acrisols and Typic Hapludult. The oil palm trees selected were 8 year old tenera (DXP ex OPRI). Each plot measured 17.6 m x 17.6 m and had 6 palm trees. There were four treatments arranged in randomized complete block design with four replicates. The treatments included: 1). TSP - OPRI fertilizer recommendation - 222 kg of AS + 222 kg of TSP + 296 kg of MOP/ha/yr (control); 2). PR1 - PR 715 kg + 222 kg of AS + 296 kg of MOP/ha - Yr 1. PR 358 kg + 222 kg of AS + 296 kg of MOP/ ha – Yr 2. PR 358 kg + 222 kg of AS + 296 kg of MOP/ha – Yr 3; 3). PR2 - PR 1428 kg + 222 kg of AS + 296 kg of MOP/ha applied once in every 5 years; 4). PR3 - PR 142.85 kg/ha +222 kg AS/ ha + 296 kg of MOP/ha applied twice in every 5 years. Application of treatments influenced the soil chemical properties to a varying extent. Gradual increase in soil nutrient lev-els were more pronounced in RP treatments than Triple Super Phosphate (TSP) treatment (control). Soil pH increased from extremely acidic (3.73) to acidic (5.43) for treatment PR2. At the end of the study, available P recorded 9.55 mg/kg. The value is slightly below the medium range of available P for oil palm production. Significant increases were recorded by RP treat-ments for exchangeable Ca, Mg, K and ECEC. The results showed that treatment PR2 was effec-tive and gave the highest oil palm yield of 62.8t/ha with TSP recording 53.7t/ha. For sustained levels of soil nutrients, growth, development and yield of oil palm, PR incorporation should be encouraged.